A Gestão do Trabalho no Sistema Único de Assistência Social: Avaliação em Processo do Mundo do Trabalho na Secretaria do Trabalho e Desenvolvimento Social no Ceará - Lima, Célia Maria de Souza Melo (2013)
The domain of this study is the analysis of Social Assistance Policy, which is conceived as a public policy, focusing on the management of work in SUAS, from a perspective of valorization of workers. This evaluative research has its empirical field of study in the Department of Labor and Social Development - STDS - that coordinates and executes the policy of Social Assistance in the state of Ceara. Thus, the object of investigation circumscribes the following dimensions about the workforce in SUAS within the STDS: way of access to public service; employment contract and remuneration; SUAS workers’ identity as a new category in the construction process; an interdisciplinary perspective on the provision of a social assistance practice to ensure social protection; continuing education as a condition for the performance of interdisciplinarity and identity formation of SUAS workers. NOB/RH - SUAS is the central reference to structure the management of work, proposing the valorization of the workers, opposing the precariousness of labor relations, as an expression of changes in the world of work in the current civilization of capital. The theoretical foundations of this study focus on the examination of the world of work and the settings of the state in capitalism, discussing their impacts in SUAS. Therefore, theorists from the critical thinking will be discussed, specially within the Marxism’s framework, giving special attention to those contemporaneous authors such as Giovanni Alves and Ricardo Antunes, contemplating formulation of state from the perspective of Nelson Coutinho and Claus Offe. In the specific field of Social Assistence Policy and its management model embodied in SUAS, analysts’ formulations are included: Raquel Raichelis, Aldaíza Sposati, Alba Carvalho, Irma Moroni Silveira and Jucimere Silveira. The importance of this study is the fact that the insertion and position SUAS workers is a current issue, which expresses itself in dilemmas in the execution of socially necessary work in the function of public management and the provision of good social assistance service to ensure social protection. The methodology circumscribes a review in process founded on a predominantly qualitative research, combined with quantitative input.